Merjalaiset - suurten järvien kansaa - Ahlqvist, Arja (Virittäjä, 1998)
The Merya - the Great Lakes people (englanti) 1/1998 (102) Arja Ahlqvist (Department of Finno-Ugrian Studies (University of Helsinki)) The Merya - the Great Lakes people A tenable etymological explanation for the ethnonym Merya has thus far been lacking. Explanations based on phonetic similarity have not resolved the problem. The writer asserts that attempts to clarify the origin of the name have not taken into consideration several very important factors that emerge only after systematic comparison of place names (toponyms). The most dominant landmarks of the area in which the ancient Merya lived are the large lakes of Central Russia: Lakes Nero and Pleshcheevo in the Yaroslavl' oblast, and Lakes Galichkoye and Chukhlomskoye in the Kostroma oblast. In each of these locations there are toponyms that feature, directly or indirectly, the root ner(V)-. In addition to the great lakes of the area that was inhabited by the Merya, there remain two more lakes in Central Russia of a similar scale: one is in the northern part of Ryazan' oblast, and the other in the eastern part of Tver' oblast; the name of both these lakes is Velikoye (< Rus. velkij 'large, immense'). On the basis of evidence provided by an extensive range of comparable and parallel toponyms, the writer demonstrates that the root ner(V)- can be seen to contain the basic element -er(o) representing the appellative *jrw 'lake' of Finno-Volgaic languages and the Uralic stem *en 'great, large' as a modifier. This can be compared, for example, with Mordvin in'e, in' 'great, large' and er'ke, R'k, jR'k 'lake' (-ke, -k is a diminutive suffix). The toponyms indicate that the ethnonym Merya was created on the basis of ner(V)- toponyms. The phonetic development required (V > and n > m) is supported by other toponyms and Russian personal names as well as Russian dialects. The original content of the root ner(V)- is therefore considered to be 'great lake'. Semantically, a similar conclusion has been reached by J. Mgiste (1966) and, in part, by A. K. Matveev (1978), who compared the name Nero with the word meri 'sea, large lake' of Finnic languages. The writer believes that the Merya would not, however, have been called the "Meri", as Mgiste assumes, but rather the "Enjrvi" ('Great lakes') people, which, in truth, they were, in the eyes of the neighbouring peoples of Central Russia. Interesting parallel cases supporting the etymology are found in toponyms of the areas inhabited by the Merya as well as in the present and former areas inhabited by other Finno-Ugrian peoples. The distribution of the ner(V)- toponyms is significantly more extensive than the area inhabited by the Merya, but even in the Merya area, connecting the origin of the root to the Merya themselves is in no way self-evident. As with many other language components present in toponyms, determining the creation and timing of the root ner(V)- is related to the broader tangle of still unresolved questions regarding the origin, distribution and interactions of the Finno-Ugrian peoples and their languages. Kielenainekset merja (kieli: suomi, sivulla: 24)